The origin and history of genetic diversity of local chickens in the Middle East and Africa - Al-Jumaili, Ahmed S. Obaid (2019)
Among the various livestock animals, chickens and their products (meat and eggs) are becoming increasingly important in sustaining human livelihood. They also represent an important model species in evolutionary studies. Today, four main types of domestic chicken may be recognised, chicken commercial breeds, fancy breeds, inbred research lines and indigenous village chicken breeds or populations. The latter are supplying high-quality protein to poor communities, particularly in Africa and Asia, contributing to food security, poverty alleviation and the management of natural resources.